Spectroscopic Evidence Against Nitric Acid Trihydrate in Polar Stratospheric Clouds - Toon, Owen B.; Tolbert, Margaret A. (1995)
Heterogeneous reactions on polar stratospheric clouds (PSC's) play a key role in the photochemical mechanisms thought to be responsible for ozone depletion in the Antarctic and the Arctic. Reactions on PSC particles activate chlorine to forms that are capable of photochemical ozone destruction, and sequester nitrogen oxides (NOx) that would otherwise deactivate the chlorine. Although the heterogeneous chemistry is now well established, the composition of the clouds themselves is uncertain. It is commonly thought that they are composed of nitric acid trihydrate, although observations have left this question unresolved. Here we reanalyse infrared spectra of type I PCS's obtained in Antarctica in September 1987, using recently measured optical constraints of the various compounds that might be present in PSC's. We find that these PSC's were not composed of nitric acid trihydrate but instead had a more complex composition perhaps that of a ternary solution. Because cloud formation is sensitive to their composition, this finding will alter our understanding of the locations and conditions in which PSCs form. In addition, the extent of ozone loss depends on the ability of the PSC's to remove NOx permanently through sedimentation. The sedimentation rates depend on PSC particle size which in turn is controlled by the composition and formation mechanism.